1999
DOI: 10.1074/jbc.274.12.7699
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Self-association of Human Recombinant Transforming Growth Factor-β3 in Aqueous Solutions

Abstract: The transforming growth factors-␤ (TGF-␤) are important regulatory peptides for cell growth and differentiation with therapeutic potential for wound healing. Among the several TGF-␤ isoforms TGF-␤3 has a particularly low solubility at physiological pH and easily forms aggregates. A spectroscopic structural analysis of TGF-␤3 in solution has thus been difficult. In this study, circular dichroism spectroscopy was used to determine the secondary structural elements of TGF-␤3. In addition, the aggregation of TGF-␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…The observed displacement of these 2 ␤-strands is even more pronounced when compared with the unbound TGF-␤3 (5 Å) and is mainly caused by adaptation to the CDR loops of GC-1008. Furthermore, the observed change in the orientation of ␣-helix 3 of TGF-␤3 was not surprising because this helix, together with its connecting loop segment, is supposed to be a rather flexible region (35,36). It allows a conformational adaptation of the TGF-␤3 homodimer to its corresponding binding partners as observed in the TGF-␤3-T␤RII complex (37), in which this region was even disordered and accompanied by a massive rearrangement of the 2 monomers.…”
Section: Discussionmentioning
confidence: 99%
“…The observed displacement of these 2 ␤-strands is even more pronounced when compared with the unbound TGF-␤3 (5 Å) and is mainly caused by adaptation to the CDR loops of GC-1008. Furthermore, the observed change in the orientation of ␣-helix 3 of TGF-␤3 was not surprising because this helix, together with its connecting loop segment, is supposed to be a rather flexible region (35,36). It allows a conformational adaptation of the TGF-␤3 homodimer to its corresponding binding partners as observed in the TGF-␤3-T␤RII complex (37), in which this region was even disordered and accompanied by a massive rearrangement of the 2 monomers.…”
Section: Discussionmentioning
confidence: 99%
“…10,24 There also have been concerns about oligomeric forms of a drug presenting an increased immunogenic risk. 25,26 For these reasons, reversible self-association interactions have been studied in almost all classes of protein therapeutics, including peptides, 27 hormones, [28][29][30] growth factors, 31 cytokines, 32 antibodies, 33,34 and recently even in single-chain Fv molecules. 35 This report is focused on characterizing the saltdependent reversible self-association pathway of a fusion protein called peptibody A (PbA).…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with our previous NMR study (13), which showed that the secondary structure and the global fold of the TGF-␤3 dimer in solution are close to those obtained for the protein crystal, but some regions are in dynamic equilibrium with an unfolded conformation. Moreover the CD studies in aqueous solution show that the ␣-helical content of TGF-␤3 in solution is less then expected from the known crystal and solution structures of TGF-␤s, including free TGF-␤3 in crystal (12). In contrast, a good agreement between the experimental CD spectrum measured in aqueous solution at pH 3.0 and CD spectrum calculated from crystal structure was found for TGF-␤2 (12).…”
Section: Experimental Relaxation Data-mentioning
confidence: 66%
“…X-ray crystallographic (9,10) and NMR (11) analyses have revealed identical folds of the TGF-␤ isoforms. However, recent studies have shown important structural differences of TGF-␤3 in solution with respect to its crystal structure and the structures of other TGF-␤s (12,13). In view of the therapeutic potential of TGF-␤, we present here a dynamic study of TGF-␤3 aimed at explaining its behavior in aqueous solution and characterizing determinants involved in the interaction with receptors.…”
Section: Transforming Growth Factors ␤ (Tgf-␤)mentioning
confidence: 99%
See 1 more Smart Citation